Criminal Responsibility Of Business Agents On Selebgram's (Celebrity Endorsers) Product Promotion - Nynda Fatmawati Octarina; Tahegga Primananda Alfath; Anisatul Ulfa (Jurnal IUS Kajian Hukum dan Keadilan, 2020)
Product promotion on Instagram by selebgram (celebrity endorser), Instagram users who have voluminous followers, is increasingly popular. It is not uncommon that the promoted products are sometimes not legally registered and possibly violate the law. This study analyses the regulations regarding promotion on social media in Indonesia as well as evaluates whether existing regulations govern business agents’ criminal Responsibility for their carried-out promotions on Instagram, as seen from the fact that such product promotion content made by selebgram has misleading information resulting consumers’ losses. The research method used is a legal research method with a regulatory approach and legal concepts. The result of this study indicates that if a business agent uploads a video which is misleading and potentially disadvantages consumers made by a selebgram, then the business agent is responsible for the upload. On social media, every user is responsible for their own account’s activities.